Respostas

2013-12-09T12:05:26-02:00
x - 2 . (3 - 2x) = 0
x - 6 + 4x = 0
x + 4x = 0 + 6
5x = 6
x = 6 : 5
x = 1,2
Resposta: x = 1,2
1 5 1
2013-12-09T12:10:34-02:00
x-2.(3-2x)=0
3x-2x²-6+4x=0
-2x²+7x-6=0

Δ = b² -4ac
Δ = 7² -4 *(-2) * (-6)
Δ = 49 -48
Δ = 1
x' = (-b + √∆)/ 2a
(-7 + 1)/2 * (-2)
(-7 + 1)/-4
-6/-4= 1,5
x'' = (-b - √∆)/ 2a
(-7 - 1)/2 * (-2)
(-7 - 1)/-4
-8/-4= 2

Verificamos quais satisfazem:

x-2.(3-2x)=0
1,5-2.(3-2.1,5)=0
1,5-2.(3-3)=0
1,5-2.(0)=0
0-0=0
0=0
Correto

2-2.(3-2.2)=0
2-2.(3-4)=0
2-2.(-1)=0
-2+2=0
0=0

Portanto tanto 1,5 como 2 pode ser o valor de x tornando a expressão verdadeira.
1 5 1